1998
DOI: 10.1097/00004647-199803000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Domain Analysis of Cerebral Blood Flow Velocity and its Correlation with Arterial Blood Pressure

Abstract: We applied frequency domain analysis to detect and quantify spontaneous fluctuations in the blood flow velocity of the middle cerebral artery (MCAFV). Instantaneous MCAFV of normal volunteers was detected using transcranial Doppler sonography. Spectral and transfer function analyses of MCAFV and arterial blood pressure (ABP) were performed by fast Fourier transform. We found the fluctuations in MCAFV, like ABP, could be diffracted into three components at specific frequency ranges, designated as high-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 33 publications
10
118
0
1
Order By: Relevance
“…Our analysis has covered up to 330 mHz range since this was the cut-off frequency of the built-in RC-filter in the fNIRS device. These bands are found to be very similar to those in related studies (Hu et al, 1999;Kuo et al, 1998;Obrig et al, 2000a;Franceschini et al, 2000;Toronov et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our analysis has covered up to 330 mHz range since this was the cut-off frequency of the built-in RC-filter in the fNIRS device. These bands are found to be very similar to those in related studies (Hu et al, 1999;Kuo et al, 1998;Obrig et al, 2000a;Franceschini et al, 2000;Toronov et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…In several other studies, three main frequency bands of interest have been identified for cerebral hemodynamics: a very low frequency VLF (8-33 mHz), a low frequency LF (around 100 mHz) named as the Mayer waves or V-signal (Mayhew et al, 1999;Obrig et al, 2000a), and a high frequency component HF (around 250 mHz), the latter being definitely synchronous with breathing rate (Kuo et al, 1998). Similarly, we conjecture that each of the canonical bands is associated with one or more of the physiological activities related to hemoglobin concentrations.…”
Section: Interpretation Of the Canonical Bandsmentioning
confidence: 95%
See 3 more Smart Citations